Upaya Perajin Pande Besi Dalam Penyediaan Stok Produksi dalam Memenuhi Permintaan Pasar Regional - Syamsul Hadi; Insan Wijaya; Risa Martha Muliasari; Muhammad Hazmi; Taufiq Timur Warisaji (Indonesian Journal Publisher, 2023)
The main equipment facilities owned by blacksmith craftsmen are generally still relatively behind compared to the progress of modern blacksmith equipment. Likewise, business managerial skills also do not use modern management which is required to manage the business effectively even though the business scale is classified as micro. The purpose of this activity is to transfer knowledge and skills in the field of appropriate technology, business management and marketing to help create economic growth and prosperity for artisans. Methods of implementing activities in the form of social engineering and technological engineering through outreach, and training using the Adult Education System. The approach taken to the engineering process is in the form of a participatory approach, empowerment and entrepreneurship building in an effort to strengthen the capacity of the target human resources by involving stakeholders with a mentoring model. The result of the implementation of the Science and Technology Program for the Community is the capacity of human resources to manage the business being developed, including the application of new technology that can run well. The economic impact is getting better because it can save costs by 39.63% and the profit rate increases by 19.37% and the work environment is more conducive